2018
DOI: 10.21037/jss.2018.03.17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interbody fusion cage on clinical and radiological outcome of surgery in L4–L5 lumbar degenerative spondylolisthesis

Abstract: In the surgical treatment of the patients with L4-L5 LDS, interbody fusion cage probably does not significantly improve the radiologic and clinical outcomes and may also be associated with more complication and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Additionally, the study of Khan et al [27] reported that TLIF for DS clinical assessment was based on VAS, with the mean preoperative VAS for back pain improving to 2 and the mean preoperative VAS for leg pain improving to 1 (0-5). Another study by Omidi-Kashani et al [28] found that, mean VAS (leg or back) improvement was comparable between the two groups, and cage application was unable to demonstrate a greater therapeutic impact. Although the TLIF group had better intervertebral union and loss of reduction, these changes were not statistically significant.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, the study of Khan et al [27] reported that TLIF for DS clinical assessment was based on VAS, with the mean preoperative VAS for back pain improving to 2 and the mean preoperative VAS for leg pain improving to 1 (0-5). Another study by Omidi-Kashani et al [28] found that, mean VAS (leg or back) improvement was comparable between the two groups, and cage application was unable to demonstrate a greater therapeutic impact. Although the TLIF group had better intervertebral union and loss of reduction, these changes were not statistically significant.…”
Section: Discussionmentioning
confidence: 92%
“…Yet, no significant difference was observed in the Oswestry Disability Index, VAS, fusion rate, and the loss of the correction between the two study groups. The authors concluded that using an interbody fusion cage did not significantly improve the radiologic and clinical outcomes of surgery in SL patients [14].…”
Section: Discussionmentioning
confidence: 95%
“…Most previous studies have focused on the relationship between cage parameters and the lumbar sagittal sequence, such as the intervertebral space height and the lordosis angle. Omidi-Kashani et al suggest that after fusion surgery at the L4-L5 level, the intervertebral fusion cage may not significantly improve the radiological and clinical outcomes but may be related to more complications and morbidity (18). Furthermore, Castellvi et al found that the best cage position for acquiring stability is near the sagittal plane's midline (19).…”
Section: Discussionmentioning
confidence: 99%